Makna Kafir dalam Al-Qur'an (Studi Komparatif Penafsiran Ibnu Kasir dan Quraish Shihab) - Ahmad Farhan; Deden Bagus Putra (IAIN Bengkulu, 2021)
The word infidel is mentioned 525 times in the Qur'an. The use of this word infidel has various meanings as in the QS. Ali 'Imran:151, the word infidels are those who associate partners with Allah while in QS. Luqman:12, the Qur'an calls the disbelievers those who disbelieve in the favors of Allah. The difference in the term infidel is not only limited to the verses of the Qur'an, but also applies among commentators, scholars, intellectuals, to ordinary people, including in the understanding of Indonesian society. This research is entitled